2003
DOI: 10.1103/physreve.67.036305
|View full text |Cite
|
Sign up to set email alerts
|

Sources and holes in a one-dimensional traveling-wave convection experiment

Abstract: We study dynamical behavior of local structures, such as sources and holes, in traveling-wave patterns in a very long ͑2 m͒ heated wire convection experiment. The sources undergo a transition from stable coherent behavior to erratic behavior when the driving parameter is decreased. This transition, as well as the scaling of the average source width in the erratic regime are both qualitatively and quantitatively in accord with earlier theoretical predictions. We also present results for the holes sent out by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…In some cases, other experimental parameters are accessible, like the depth of the heated wire below the surface [28,29]. Such changes will affect the coefficients of the CGLE, although often these are not known, let alone their dependence on experimental parameters.…”
Section: Incoherent Dynamics and Experimentsmentioning
confidence: 99%
“…In some cases, other experimental parameters are accessible, like the depth of the heated wire below the surface [28,29]. Such changes will affect the coefficients of the CGLE, although often these are not known, let alone their dependence on experimental parameters.…”
Section: Incoherent Dynamics and Experimentsmentioning
confidence: 99%
“…Phase matching at defects has recently been discussed quite extensively in the physics literature [23,1,36,37]. To explain this issue, we fix a continuous function ϑ(k) and define the phase of a wave train to be its argument…”
Section: Phase Matchingmentioning
confidence: 99%
“…The recent experiments in [1,36,37], in which nonlinear waves and various kinds of defects were triggered by heated wires immersed in thin layers of oil, were motivated by the desire to obtain a quantitative comparison with coupled Ginzburg-Landau equations. Other experiments where defects have been observed are the printer instability [19], laterally heated fluid layers [4], and thermal convection of binary fluids [31].…”
Section: Introductionmentioning
confidence: 99%
“…3 above will have both real and imaginary parts. A direct comparison of experiment with CGLE-based theory can be difficult, because the CGLE can describe an extraordinary variety of different traveling-wave dynamics, and the coefficients of the equation are in general difficult to determine experimentally [50]. However, it is well-known that a reduction of the dimensionality or localization in the experimental patterns, which have both been achieved in the present experiments by using a long strip of laser light to localize the rolls, can reduce considerably the difficulty of determining the coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well-known that a reduction of the dimensionality or localization in the experimental patterns, which have both been achieved in the present experiments by using a long strip of laser light to localize the rolls, can reduce considerably the difficulty of determining the coefficients. A useful starting point would appear to be the CGLE modeling approach adopted by Pastur et al [50] in describing their heated-wire experiments. These authors observed leftand right-traveling waves separated by sources and sinks.…”
Section: Discussionmentioning
confidence: 99%